TINDAK KEKERASAAN TERHADAP ISTERI DALAM UU NO 23 TAHUN 2004 DAN HUKUM ISLAM - Tasriani Tasriani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2010)
This article discussed the violence in domestic area especially the violence against the househould in the perspective of the act No 23 of 2004 and the Islamic law. Both the act No 23 of 2004 and the Islamic law have the same spirit that is respect to woman prestige, especially househoul and fight against discrimination. In the act No 23 of 2004 is stated regarding the rule of its crime, while in the Islamic law does not stated it. Islamic law just returned it to the concept of marriage in Islam which known as the concept of sakinah, mawaddah, warahmah. It is clear that the violence againts the househould is not enabled in the perspective of the act No 23 of 2004 and the Islamic law.